Efeito do tratamento de soja (Glycine max (L.) Merril) com óleo mineral sobre a emergência das plântulas e sobre a nodulação radicular - Gonçalves Brasileiro, Beatriz; Silva Reis, Múcio; Sediyama, Tuneo; Sigueyuki Sediyama, Carlos; Lopes Gomes, José Luiz (Revista Ceres, 2025)
Six soybean genotypes: Cristalina, Doko, Uberaba, UFV 81-234, UFV 80- 135 and UFV 83-355 harvested at R8 and R8 + 30 days after maturity were submitted to seed treatment with 400 ml of diesel oil per 100 kg of seeds to verify the emer- gence of seedlings under green house conditions. The cultivar Uberaba was used to verify the effect of seed treatment with diesel oil at a level of 400 mil/100 kg of seeds and treatment with commercial Bradyrhizobium Japonicum at a level of 200 £/40 kg of seeds on soybean nodulation using both soil that had been cultivated and soil that had not been cultivated with soybean. The percentage of seed germi- nation and the speed index of seed germination were not decreased by diesel oil treatment; root nodulation was influenced by soil type and seed inoculation. Seed treatment with diesel oil did not decrease the number of nodules per plant, which Was considerably greater in the soil where soybean had previously been cultivated, The number of active root nodules also was not decreased by diesel oil treatment.